Firm Sizie as a Key Factor in Asset Pricing: a Systematic Literature Review of the Fama-French Models - Tri Haryanto; Ratih Huriryati; Lisnawati Lisnawati (Jurnal Sosial Teknologi, 2025)
This study aims to analyze the impact of system responsiveness to service disruptions on the utilization rate of the Palapa Ring public digital network from a strategic marketing perspective. The focus is on operational data, particularly the number of disruptions and their resolution ratio (SLA Resolution Rate), which represent the marketing intelligence system applied in public service management. Due to the unavailability of complete technical data such as uptime and latency, this research adopts a quantitative approach using secondary data from the Palapa Ring ticketing report system for 2024–2025. Network utilization is calculated using a proxy approach based on the ratio between unresolved and resolved disruptions. Regression analysis results show that the SLA Resolution Rate significantly and positively affects network utilization, while the number of disruptions has a negative but relatively minor effect. These findings highlight the importance of efficient disruption handling as a key factor in maintaining user trust and participation in public digital services. The study contributes to the application of sustainability marketing and marketing intelligence concepts in managing national digital infrastructure, emphasizing the need for performance transparency and reporting systems as strategies to enhance digital public service adoption and accountability.